THE ROLE OF SPORTS BROADCASTS IN GAINING COMPETITIVE ADVANTAGE BY TV STATIONS - Ewa Jaska (Acta Scientiarum Polonorum. Oeconomia, 2018)
The aim of this paper is to explore the role of sports broadcasts in achieving competitive advantage by TV stations over their rivals on the basis of primary and secondary sources. Firstly, the study provides a review of the transformations of the television market in Poland resulting in more intense search for new content and sources of funding. Secondly, it presents analysis of viewership and advertising revenues of TV stations holding rights for sports broadcasts. Finally, it investigates what factors determine viewers’ decision to pay for premium content. The conducted analysis covers broadcasts of selected sporting events, namely football matches played as part of championships and ski jumping. TV stations holding rights to broadcast important sports events have higher advertising revenues, bigger audience market shares and launch additional channels, special platforms and use social media to deliver their content to all segments of the audio-visual market.